Assessment of storage behavior of antibiotics and influence factors among household members in Boyolali, Indonesia: A cross-sectional study - Hidayah, Karuniawati; Roshiedah, Abdul Rahman; Hossain, Md Sanower; Arifah Sri, Wahyuni; Dinda Zanur’aini Aulia, Hakim; Ikhwan Yuda, Kusuma (Bentham Science Publishers, 2025)
Introduction: Storing antibiotics at home is common in many developing countries, often leading to irrational use and increasing the risk of antibiotic resistance. This study assessed antibiotic storage practices, reasons for storage and use, knowledge levels, and household influencing factors. Methods: A cross-sectional online survey with a validated questionnaire was conducted from November 2021 to January 2022 in the Boyolali Regency, Central Java, Indonesia. The inclusion criteria were as follows: resident of Boyolali, 18-65 years old, used antibiotics and could fill out a questionnaire. The exclusion criteria were respondents who had no internet access. Descriptive, bivariate, and multivariate analyses were performed, with statistical significance set at p < 0.05. Results: Of the 407 respondents, most were aged 18–25 years (71.7%), female (71.7%), single (75.2%), and had a senior high school education (61.4%). Antibiotics, primarily amoxicillin and tetracycline, were the second most commonly stored drugs (19%) after analgesics/antipyretics. Common reasons for storage included preparation for sudden illness (40.4%), leftover prescriptions (38.6%), and ongoing treatments (13.2%). Self-medication was reported by 45.2% of participants. Although 68.3% had moderate knowledge, inappropriate storage and use remained prevalent. Key factors significantly associated with antibiotic storage practices included the last time the antibiotic was used less than three months (p=0.001), having a family member in the healthcare field (p=0.01), and low and moderate antibiotic knowledge scores (p=0.002). Discussion: The findings underscore the ongoing public health challenge of inappropriate antibiotic storage and selfmedication, even among individuals with moderate knowledge. These behaviors contribute to the misuse of antibiotics and potentially drive antimicrobial resistance, aligning with concerns raised in prior research from other low- and middle-income settings. The study reinforces the role of household factors, such as recent antibiotic use and family healthcare background, in influencing storage practices. However, limitations include reliance on self-reported data and the use of an online survey, which may not capture perspectives from less internet-accessible populations. Conclusion: Despite moderate awareness, inappropriate antibiotic use and storage are widespread, underscoring persistent behavioral gaps. These findings highlight the need for targeted public health campaigns and communitylevel interventions to promote responsible antibiotic practices and mitigate antimicrobial resistance risks.